Construction of decision support system for strategic management on the basis of complex goal program apparatus - Azarova, A. O.; Foronova, O. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The complex goal program (CGP) and structural hierarchical model of DSS formalization for enterprise strategic management are presented in the paper. It is based on the using of alternatives hierarchical goal estimation, i.e. on determination of relative coefficients of any project realization influence on the ability to reach the main goal - effective management. To determine these indices the decomposition of the main goal and the formation by experts’ goal hierarchy are performed.